2009
DOI: 10.1002/aic.11817
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of velocity distribution among microchannels with triangle manifolds

Abstract: A model of velocity distribution among microchannels with triangle manifolds is proposed. According to the flow behaviors analyzed by Fluent, the manifolds are divided into several approximate rectangular channels, and then an equivalent simplified resistance network model is developed to establish the relationships between the velocities and pressure drops in microchannels and approximate rectangular channels. The velocity distributions are calculated under two situations, respectively, considering and ignori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 12 publications
(16 reference statements)
1
47
0
Order By: Relevance
“…Microchannel structure plays an important role in catalyst coating, velocity distribution of reactant among microchannels and heat-transfer efficiency. Reasonable microchannel structure can effectively improve the velocity uniformity among parallel microchannels, which leads to uniform residence time distribution among microchannels and hence improves the conversion rate and selectivity of process [10][11][12]. Parallel and uniform-distributed microchannels with rectangular cross-section were generally adopted in a majority of researches [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Microchannel structure plays an important role in catalyst coating, velocity distribution of reactant among microchannels and heat-transfer efficiency. Reasonable microchannel structure can effectively improve the velocity uniformity among parallel microchannels, which leads to uniform residence time distribution among microchannels and hence improves the conversion rate and selectivity of process [10][11][12]. Parallel and uniform-distributed microchannels with rectangular cross-section were generally adopted in a majority of researches [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work [8], we proposed a theoretical model to study the characteristics of velocity distribution among microchannels with triangle manifolds. A simplified method was developed by dividing the manifolds into multiple approximate rectangular channels based on the pressure distribution simulated by Fluent TM .…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that microreactor devices run safely under conditions, which lay in the explosion regime [22,[29][30][31]. For instance, the strongly exothermic o-xylene oxidation to phthalic anhydride was operated safely in the explosive regime in a microfixed bed reactor at high temperature [32,33]. Usually, microreactors are operated under laminar flow conditions.…”
Section: Introductionmentioning
confidence: 99%